Pengaruh Job Demands, Dukungan Sosial Suami, dan Faktor Demografi terhadap Work-Family Conflict Karyawati Bank yang telah Menikah - Mega Anggraeni; Zulfa Indira Wahyuni (Universitas Kristen Maranatha, 2019)
Abstrack Women who are married and decide to keep working will add another role in their lives. Work-family conflict occurs when the roles and responsibilities between work and family are not balanced so that it will cause pressure and conflict that can disrupt the balance between work and one's person. This study aims to examine the effect of job demands (work overload, cognitive demand, and emotional demand), social support husband (emotional support, informational support, instrumental support, and support friendship) and factor demographic on work-family conflict of married bank employees. This study was conducted to 160 bank employees who are married and have children. The sampling technique used is non-probabililty sampling technique that is purposive sampling. The author uses Work-Family Conflict Scale (WFCS) measuring instruments developed by Carlson, Kacmar & Williams (2000), Questionnaire On The Experience And Assessment Of Work from Bakker, Brummelhuis, Prins & Heijden (2011) and husband's social support developed from Sarafino's (2011) social support theory. The validity of measuring equipment using confirmatory factor analysis technique (CFA) with the help of software Lisrel 8.70 and the data analysis using multiple regression analysis techniques with the help of software SPSS 22.0 The results of research using multiple regression analysis showed that all the free variables used significant effect against the work-family conflict with the proportion of variants of 55.4%, while the remaining 44.6% are influenced by variables other than research. Meanwhile, the results of the analysis of each variable separately variable indicates that work overload, cognitive demand and emotional demand significantly to work-family conflict in married employees. While the variables of emotional support, informational support, instrumental support, support friendship, working hours, number of children, and age of the last child not significant effect on work-family conflict of married bank employees. Keywords: Work-Family Conlict, job demands, social support husband